2009
DOI: 10.1016/j.cogpsych.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The relations between children’s communicative perspective-taking and executive functioning

Abstract: Two experiments investigated children's communicative perspective-taking ability. In Experiment 1, 4- to 5-year-old children were tested on two referential communication tasks, as well as on measures of inhibitory control, working memory, and cognitive flexibility. Results document children's emergent use of the perspective of their speaking partner to guide their communicative behaviors in both a production and comprehension task. In Experiment 2, 3- to 4-year-old children used a speaker's perspective to guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
284
8
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(313 citation statements)
references
References 97 publications
(114 reference statements)
18
284
8
3
Order By: Relevance
“…Although sensitivity to a communicative partner's perspective emerges as early as 3 to 5 years of age (Nadig & Sedivy, 2002;Nilsen & Graham, 2009), there is a continuous reduction of egocentric errors on communication tasks between age 7 and 17 years (Dumontheil et al, 2010). That a continuous improvement is seen after the age at which children pass conceptual tests of visual perspective (Moll & Tomasello, 2006) and theory of mind (Wellman et al, 2001;Wimmer & Perner, 1983) suggests that the improvement is likely driven by an advancing ability to use perspectival information rather than acquiring further understanding of others' perspectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sensitivity to a communicative partner's perspective emerges as early as 3 to 5 years of age (Nadig & Sedivy, 2002;Nilsen & Graham, 2009), there is a continuous reduction of egocentric errors on communication tasks between age 7 and 17 years (Dumontheil et al, 2010). That a continuous improvement is seen after the age at which children pass conceptual tests of visual perspective (Moll & Tomasello, 2006) and theory of mind (Wellman et al, 2001;Wimmer & Perner, 1983) suggests that the improvement is likely driven by an advancing ability to use perspectival information rather than acquiring further understanding of others' perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The only direct evidence on factors affecting children's use of perspective information comes from Nilsen and Graham (2009), who found that higher rates of egocentric errors were associated with poorer inhibitory control. Similar trends were observed for measures of working memory though these effects did not reach significance.…”
Section: Introductionmentioning
confidence: 99%
“…Although subsequent research has shown that children aged around 4 or 5 (Nilsen & Graham, 2009), 5 or 6 (Bahtiyar & Küntay, 2008;Nadig & Sedivy, 2002) show sensitivity to the addressee's perspective in the production of contrastive adjectives, research has also shown that unlike adults, AUDIENCE DESIGN IN CHILDREN 6 words to novel referents like children without ASD (Tek, Jaffery, Fein, & Naigles, 2008) and use the same contextual information as their controls when doing so (De Marchena, Eigsti, Worek, Ono, & Snedeker, 2011;Preissler & Carey, 2005). When producing sentences, high-functioning children with ASD can also align sentence structures with their partner, demonstrating unimpaired syntactic representations (Allen, Haywood, Rajendran, & Branigan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These are general cognitive processes that define and maintain the individual's goals, recruit appropriate perceptual and response mechanisms, and monitor their performance (e.g., Norman & Shallice, 1986;Posner & Petersen, 1990). When we speak, we need to choose our words wisely (e.g., considering our goals and the common ground between interlocutors; Nilsen & Graham, 2009;Ye & Zhou, 2009), allocate sufficient processing capacity to our speech planning processes (e.g., Cook & Meyer, 2008;Ferreira & Pashler, 2002;Roelofs, 2008aRoelofs, , 2008b, and monitor our speech output for appropriateness and correctness. We also need to choose and maintain an appropriate speech rate and register (e.g., child-directed speech or the formal style required for a sermon, see Meyer, Konopka, Wheeldon, & van der Meulen, 2012).…”
mentioning
confidence: 99%